Modernisasi Melunturkan Kepercayaan Masyarakat Suku Jawa Yang Mengarah Pada Kehidupan Sekuler - Jahra Sinaga, Fadhillatu; Ade Chandra, Fadhlin (Yayasan Darussalam Bengkulu, 2021)
The rapid development of modernization towards the flow of technological advances makes the Javanese tribal society gradually eliminate mystical beliefs so that religious rituals are rarely carried out except for the royal family who still carry out these religious rituals. A life that puts the world first is secular. At first, many Javanese people believed in ancestral customs, although basically the Javanese people had religion, such as witchcraft, wangsit and other mystical things. Javanese society prioritizes harmony and respect as an effort to maintain the harmony of life